1963
DOI: 10.1037/h0038722
|View full text |Cite
|
Sign up to set email alerts
|

A note on the effects of score transformations in Q and R factor analysis techniques.

Abstract: In a recent article in this journal addressed to the effects of score transformations in Q and R factor analysis techniques, Broverman (1961) claims to have presented ". . . new arguments and empirical evidence of important differences not previously recognized between the two techniques as they are commonly employed." These differences are said to include "differences in results, differences in the type of inference possible from the results, and consequently differences in the theoretical implications of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1964
1964
1983
1983

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Elimination of the "g" factor through "ipsatization" of scores, that is, expressing individual scores as deviations from the individual's general level of performance, has consistently produced bipolar factors in which simple perceptual-motor and inhibitory restructuring tasks are contrasted (Broverman, 1964), and which are related in the expected directions to physical indices of androgen stimulation (Broverman et al, 1964). However, since the removal of "g" variance, either by ipsatization or by standard factor extraction procedures, tends to artifactually induce negative relationships in the residual variance (MacAndrew & Forgy, 1963;Ross, 1963), such oppositions between abilities have been necessarily interpreted cautiously as statis-tical rather than functional expressions of relationships between abilities. Unfortunately, no unambiguous statistical method of demonstrating inverse relationships between abilities in the presence of an overriding "g" factor exists.…”
Section: Implications Of Physiological Hypothesis Of Sex Differences ...mentioning
confidence: 99%
“…Elimination of the "g" factor through "ipsatization" of scores, that is, expressing individual scores as deviations from the individual's general level of performance, has consistently produced bipolar factors in which simple perceptual-motor and inhibitory restructuring tasks are contrasted (Broverman, 1964), and which are related in the expected directions to physical indices of androgen stimulation (Broverman et al, 1964). However, since the removal of "g" variance, either by ipsatization or by standard factor extraction procedures, tends to artifactually induce negative relationships in the residual variance (MacAndrew & Forgy, 1963;Ross, 1963), such oppositions between abilities have been necessarily interpreted cautiously as statis-tical rather than functional expressions of relationships between abilities. Unfortunately, no unambiguous statistical method of demonstrating inverse relationships between abilities in the presence of an overriding "g" factor exists.…”
Section: Implications Of Physiological Hypothesis Of Sex Differences ...mentioning
confidence: 99%
“…The analysis of the raw data yielded the usual factors of evaluation, potency, and activity, but when only intraindividual variability was analyzed, the results were different. MacAndrew and Forgy (1963) have criticized Broverman's findings on the basis that Broverman's method of factor extraction produced rotated factors, and when rotated factors extracted from the principle components R technique was used, the results were comparable. The present study, however, revealed distinct differences between the rotated factor structure of the raw scores and the double standardized scores even though a principal axis solution was used in both instances.…”
Section: Resultsmentioning
confidence: 85%
“…Ipsatization of scores removes normative differences between individuals which would otherwise appear as the first "g" factor in a factor analysis of normative scores (Broverman, 1963;MacAndrew & Forgy, 1963;Ross, 1963). Factors extracted from the remaining within-individual variance, either by analysis of ipsative scores, or as residual factors in a centroid analysis of normative scores, are necessarily bipolar.…”
Section: (1958)mentioning
confidence: 99%